A systematic review of imaging findings in patients with Osgood‐Schlatter disease. Issue 6 (2nd October 2021) - Sørensen, Line Bay; Rathleff, Michael Skovdal; Dean, Benjamin John Floyd; Oei, Edwin; Magnusson, Stig Peter; Olesen, Jens Lykkegaard; Holden, Sinéad
Abstract: This systematic review aimed to describe the imaging characteristics of Osgood‐Schlatter (OSD) compared with controls and imaging findings over time. A systematic search was conducted in Embase, CINAHL, and PubMed from inception until July 2021. Forty studies were eligible and included based on inclusion criteria on OSD diagnosis, the number of patients, and imaging outcomes. In patients with OSD, but not controls, findings were soft‐tissue swelling of the cartilage and infrapatellar bursa, tendon changes, increased Doppler flow, and fragmentation of the secondary ossification center. Follow‐up studies reported improvements over time, but some identified persistent tendon thickening and/or ossicles. Adults with OSD generally present with free ossicles. Findings were inconsistent on whether different morphometric features were altered in OSD compared to controls. OSD patients were classified within the early stages of tibial tuberosity maturation. This review documents that OSD presents with tissue alterations that do not appear in controls or the patient's asymptomatic knee. Notably, a large portion had tendon involvement, and ossicles seem to be associated with residual symptoms after maturation. Standard imaging of adolescents with OSD needs to be carefully considered when determining if tissue alterations are related to disease progression or part of the normal maturation.